Migration Prediction Model of Residual Contaminants from Food Packaging Paper and its Experimental Verification. (28th December 2012) - Huang, Chong‐Xing; Duan, Dan‐Dan; Yan, Meng‐Meng; Wang, Shuang‐Fei
Abstract : A migration prediction model of residual contaminants from food packaging paper was established on the basis of one‐dimensioned Fick's diffusion theory, and analytical solutions were obtained by inducing paper porosity and the adsorption quantity of pollutants. In addition, the migration of the six contaminants, namely styrene, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, dioctyl phthalate and bisphenol A in three kinds of food packaging paper(Kraft, white cardboard and imitation parchment) into different food stimulants was studied. In this study, the diffusion coefficient and the partition coefficient of these six contaminants in those papers were measured by experiments, and the experimental migration data and calculated values based on the model were analyzed. The results show that paper porosity affects the migration of contaminants so significantly that it is necessary to set it as a parameter in the analysis model. The experiment results agreed with the theoretical prediction values when the temperature was set approximately at 25°C. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : A migration prediction model of residual contaminants from food packaging paper was established on the basis of one‐dimensioned Fick's diffusion theory, and analytical solutions were obtained by inducing paper porosity and the adsorption quantity of pollutants. In addition, the migration of the six contaminants in food packaging paper into different food stimulants was studied. The diffusion coefficient and the partition coefficient of these six contaminants in those papers were measured by experiments, and the experimental migration data and calculated values based on the model were analyzed.